Online Survey System (OSS) / Tan Hui Min - Tan, Hui Min (2001)
Online survey system (OSS) is an electronic survey system and productivity tool. The system enables the user to conduct a survey at case which was previously paper-based and which can be tedious and time-consuming. It can be used or administered from anywhere an internet browser is available. The users can create and design their own interactive online survey. OSS provides a fast distribution of survey from to a large geographical area through email. The respondents just need to click on the URL attach with the invitation email to direct them to the survey. After that OSS will generates analysis report based on the responses collected. User will be able to get the results such as average percentage, etc by mouse click.